Effects of Sponsorships on Performance of Para Athletes in Kenya - Kiptembur, John K.; Ng’ang’a, Dr. Wambui; Makomere, Dr. Julie; Otuya, Prof. Robert (African Journal of Education,Science and Technology (AJEST), 2024)
Sponsorship is used throughout a Para Athlete career beginning from when talent is identified and trained, to when they participate and perform at athletics competitions. The study aimed at investigating how sponsorship approaches affect Para Athletes performance. These aspects include the athletics expertise, competitive style, sportsmanship and rivalry obtained from conceptual Model of Athlete Brand Image. An exploratory case study was done to twenty (20) Para Athletes after theoretical sampling from the total sixty six (66) Para Athletes. In-depth interviews and observation were used to collect data among the Para Athletes. Validity and reliability were tested using pilot study on five (5) Para Athletes. The data analysis was done guided by Grounded Theory research design using the Straussian Approach. The study found that sponsorships were not there for the Para Athletes and hence no effect was experienced on their performance. Two major themes were identified with respect to the sponsorships on performance of Para Athletes. First, the Para Athletes acknowledged extremely limited interaction to sponsorships, with some none at all. Secondly, the Para Sport structure and leadership proved to explain the nature of current sponsorships. Hence, appropriate Para Athletics leadership and structure to drive the availability and use of sponsorships in Para Athletics is vital. The implication of these findings is to reorganize the structure and method of selecting Kenya's Paralympic leadership, which should be included in the federation constitution. Based on the findings of the study, further research should be done to develop appropriate Para Sport structure and leadership to influence sponsorships and Para Athlete performance.